Syria's reconstruction scramble: In a game fraught with political risk, Europe should aim for long-term stabilization - Muriel Asseburg; Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2017)
By November 2017, as the civil war abated and the so-called Islamic State (IS) was all but defeated, Moscow increased its efforts to reach what it regards as conflict resolution in several fora beyond the UN-led Geneva process. Moreover, as the US administration made it clear that it would not be engaging in reconstruction efforts, Russia has sought Euro-pean financial assistance to help cover the costs of rebuilding the country, together with Arab Gulf states. Although the European Union had, in April 2017, ruled out support for reconstruction without a political transition, calls have now been mounting in Europe to accommodate Bashar al-Assad, help in the reconstruction of Syria, and send back refugees. Yet, the fighting is far from over. More importantly, the mere reconstruction of physical infrastructure would do little to instill stability, but would rather raise the risk of fueling new conflicts. Europeans should therefore make clear to Russia that they will stick with their own approach. They should play the long game and develop leverage to make future contributions serve state- and peace-building purposes. Meanwhile, they should focus on increased levels of humanitarian aid, early recovery measures, such as de-mining and restoring basic water and health infrastructure, building human capital in Syria and among Syrian refugee communities, in addition to concentrating on civil society and local governance support where they have credible partners
Keywords: 320